Kandungan Metabolit Sekunder dan Aktivitas Tanaman Bajakah Sebagai Agen Antioksidan - Winney Amiani; Muhammad Ricko Fahrizal; Reza Nathasya Aprelea (Syntax Corporation Indonesia, 2022)
The increase in free radicals can cause oxidative damage from the cellular, tissue, and organ levels. Therefore, antioxidant compounds are needed to stabilize free radicals. One of the plants that has antioxidant activity is bajakah. This study aims to determine the content of secondary metabolites and bajakah activity as an antioxidant agent from various literature studies. The method used is Literature Review Article. The data are articles, national and international, published in 2012-2022 that match the keywords and are searched using the Google Scholar, Research Gate, and PubMed databases. After the screening process, 5 literatures were obtained which were further reviewed. Based on the results of a review of the literature, bajakah showed antioxidant activity which was classified as strong and very strong because it had an IC50 value below 100 ppm. This antioxidant activity is due to the content of secondary metabolites such as flavonoids, phenolics, saponins, tannins owned by bajakah.